1996
DOI: 10.2466/pms.1996.83.3f.1235
|View full text |Cite
|
Sign up to set email alerts
|

The Method of Subliminal Psychodynamic Activation: Do Individual Thresholds Make a Difference?

Abstract: The present experiment investigated the effects of subliminal psychodynamic stimuli on anxiety as measured by heart rate. Following an anxiety-inducing task, male and female subjects were tachistoscopically shown, at their subjective thresholds, one of five subliminal stimuli, MOMMY AND I ARE ONE, DADDY AND I ARE ONE (symbiotic messages). MOMMY HAS LEFT ME (abandonment message), I AM HAPPY AND CALM (positively toned but nonsymbiotic phrase), or MYMMO NAD I REA ENO (control stimulus). It was hypothesized that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Next, it is focused on the high level of cognitive during in the class, by applying (C3), analyzing (C4) and evaluating (C5) (Paristiowati et al, 2017). Another research shows that the approach of a problem oriented can impact promise to chemical learning in developing the ability of high-order thinking and students' scientific literacy (Malik, Paraherakis, Joseph, & Ladd, 1996;Marks & Eilks, 2009).…”
Section: Results and Findingsmentioning
confidence: 99%
“…Next, it is focused on the high level of cognitive during in the class, by applying (C3), analyzing (C4) and evaluating (C5) (Paristiowati et al, 2017). Another research shows that the approach of a problem oriented can impact promise to chemical learning in developing the ability of high-order thinking and students' scientific literacy (Malik, Paraherakis, Joseph, & Ladd, 1996;Marks & Eilks, 2009).…”
Section: Results and Findingsmentioning
confidence: 99%
“…Theory and findings regarding SPA effects have received critical feed-back raising issues relating to the appropriateness of control and threshold stimuli in the various experiments [23,24], the possible need for physiological indicators of anxiety reduction such as the subject's heart rate in addition to the psychological measures [25], and questions about the need for neutral, i.e., neither drive-nor affect-related, stimuli to establish individual subjective thresholds for SPA [26]. However, quantitative and qualitative reviews and meta-analyses of research conducted over the years lead to the conclusion that the major findings remain statistically significant [27].…”
Section: Non-conscious Perception Influencing Conscious Cognition And...mentioning
confidence: 99%
“…Some restricting effect of awareness on psychodynamic responsiveness is widely believed to diminish the efficiency of relaxation techniques that combine soothing music with verbal suggestions, which has lead to the sustained use of subliminal suggestions combined with soft music in relaxation therapy. Experimental studies have shown that the most efficient combinations appear to be indeed those where soft music is presented together with verbal stimuli of intensities below the level of conscious perception [22].Theory and findings regarding SPA effects have received critical feed-back raising issues relating to the appropriateness of control and threshold stimuli in the various experiments [23,24], the possible need for physiological indicators of anxiety reduction such as the subject's heart rate in addition to the psychological measures [25], and questions about the need for neutral, i.e., neither drive-nor affect-related, stimuli to establish individual subjective thresholds for SPA [26]. However, quantitative and qualitative reviews and meta-analyses of research conducted over the years lead to the conclusion that the major findings remain statistically significant [27].…”
mentioning
confidence: 99%